SPECTRAL CHARACTERISTICS OF NOISE IN THE WORKERS OF MAIN DEPARTMENTS OF THE ENTERPRISES OF ALUMINIUM AND THERMAL POWER INDUSTRIES - E. A. Panaiotti; I. P. Danilov; D. V. Surzhikov (Acta Biomedica Scientifica, 2013)
The study of the spectral characteristics of noise levels in the workers of main departments of the enterprises of aluminium and thermal power industries had shown that equivalent sound levels in electrolysis shops at the workplaces of those engaged in electrolysis and anodic production exceeded permissible indicators on 7,1 and 11,8 dBA; in boiler shops of a thermal power station at the workplaces of boiler machinists, machinists-inspectors of boiler equipment and mill machinists the excess in permissible indicators was 22,2 dBA, 21,4 dBA and 29,3 dBA accordingly. It was established that noise in boiler and turbine shops of a thermal power station was broadband and exceeded maximum permissible values in all parts of a spectrum. In the turbine shops of a thermal power station noise levels more often exceeded maximum permissible levels in low- and high-frequency parts of a spectrum.